Homogeneous Canine Chest Phantom Construction: A Tool for Image Quality Optimization - Menegatti Pavan, Ana Luiza [UNESP]; Dela Rosa, Maria Eugenia [UNESP]; Giacomini, Guilherme [UNESP]; Bacchim Neto, Fernando Antonio [UNESP]; Yamashita, Seizo [UNESP]; Vulcano, Luiz Carlos [UNESP]; Duarte, Sergio Barbosa; Arruda Miranda, Jose Ricardo de [UNESP]; Pina, Diana Rodrigues de [UNESP] (Public Library Science, 2016)
Digital radiographic imaging is increasing in veterinary practice. The use of radiation demands responsibility to maintain high image quality. Low doses are necessary because workers are requested to restrain the animal. Optimizing digital systems is necessary to avoid unnecessary exposure, causing the phenomenon known as dose creep. Homogeneous phantoms are widely used to optimize image quality and dose. We developed an automatic computational methodology to classify and quantify tissues (i.e., lung tissue, adipose tissue, muscle tissue, and bone) in canine chest computed tomography exams. The thickness of each tissue was converted to simulator materials (i.e., Lucite, aluminum, and air). Dogs were separated into groups of 20 animals each according to weight. Mean weights were 6.5 +/- 2.0 kg, 15.0 +/- 5.0 kg, 32.0 +/- 5.5 kg, and 50.0 +/- 12.0 kg, for the small, medium, large, and giant groups, respectively. The one-way analysis of variance revealed significant differences in all simulator material thicknesses (p < 0.05) quantified between groups. As a result, four phantoms were constructed for dorsoventral and lateral views. In conclusion, the present methodology allows the development of phantoms of the canine chest and possibly other body regions and/or animals. The proposed phantom is a practical tool that may be employed in future work to optimize veterinary X-ray procedures.